Geografia do Brasil: uma questão de discurso - Bruna Torres Batista (2019)
This study aims to understand the discursive construction of the discipline Geography of Brazil at the Faculty of Philosophy of Minas Gerais. The idea was to research about the principles that governed the foundations of this discipline in Minas Gerais and Brazil, inscribing in a healthier way the participation of the Minas Gerais Geography course in the History of Brazilian Geographic Thought. We try to understand how this discipline organized and built its discourse about Brazil, how this country was viewed from Minas Gerais. To achieve these goals we worked with Discourse Analysis in the meeting of three theorists: Foucault, Bakhtin and Pêcheux. Discourse Analysis provided us with the theory and methodology needed to investigate the discursive construction of the discipline, as well as orienting the most forceful study of geographical discourses in their elaboration and circulation. The analysis allowed us to see how the discipline Geography of Brazil became a possible utterance and which enunciative contexts guided the formulation about the discourse about Brazil. This discipline emerged in a context that strived to renew the methodology and theory of geography making it more scientific. At the same time, it was in the twentieth century the result of curricular reforms implemented by the Brazilian government. The consensus was that geography was one of the instruments for the consolidation of patriotic sentiment in the country. It arises first in school knowledge and only then be institutionalized in the Academy. But, this was not an obvious move. At the Federal College of Minas Gerais it was organized according to what was understood by the method of geographical possibilism and had a very strong dialogue with the Brazilian state organizing and designing this country according to the ideology of progress. Its main objective was to enunciate Brazil as a country of possibilities and future. In addition, there was an intense need to legitimize geographical knowledge as a scientific discipline and necessary for the Brazilian nation.